2018
DOI: 10.1080/01677063.2018.1461866
|View full text |Cite
|
Sign up to set email alerts
|

Two novel forms of ERG oscillation inDrosophila: age and activity dependence

Abstract: Over an animal's lifespan, neuronal circuits and systems often decline in an inherently heterogeneous fashion. To compare the age-dependent progression of changes in visual behavior with alterations in retinal physiology, we examined phototaxis and electroretinograms (ERGs) in a wild-type D. melanogaster strain (Canton-S) across their lifespan. In aged flies (beyond 50% median lifespan), we found a marked decline in phototaxis, while motor coordination was less disrupted, as indicated by relatively stronger ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Thus, one limitation to our study is that we have not directly shown which phototransduction proteins are responsible for the ERG phenotype. Other groups have performed ERGs in old flies and observed decreased transient amplitudes [ 106 ], differing from our observations under blue light, consistent with the idea that the different phototransduction proteins identified as oxidized under each condition result in different physiological outcomes. Since we only measured glutathione ratios in the eye under light stress and aging, which is a limitation of our study, it is possible that there could be changes in the levels and/or localization of specific ROS under these two different conditions.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, one limitation to our study is that we have not directly shown which phototransduction proteins are responsible for the ERG phenotype. Other groups have performed ERGs in old flies and observed decreased transient amplitudes [ 106 ], differing from our observations under blue light, consistent with the idea that the different phototransduction proteins identified as oxidized under each condition result in different physiological outcomes. Since we only measured glutathione ratios in the eye under light stress and aging, which is a limitation of our study, it is possible that there could be changes in the levels and/or localization of specific ROS under these two different conditions.…”
Section: Discussionsupporting
confidence: 87%
“…In parallel, sev eral established behavioral assays have provided readouts of age-related functional decline, including fast phototaxis and negative geotaxis ( Miquel et al, 1976 ; Arking and Wells, 1990 ; Simon et al, 2006 ), flight ( Miller et al, 2008 ), memory ( Tamura et al, 2003 ; Yamazaki et al, 2007 ), courtship ( Cook and Cook, 1975 ; Partridge et al, 1987 ), as well as sleep and other circadian activity patterns ( Koh et al, 2006 ; Bushey et al, 2010 ). However, behavior-relevant studies registering concomitant changes in neurophysiological processes in Drosophila have been largely limited to electroretinogram ( Ueda et al, 2018 ), peripheral neuromuscular synapses ( Banerjee et al, 2021 ), or GF pathway SLR properties ( Martinez et al, 2007 ; Augustin et al, 2018 , 2019 ; Blagburn, 2020 ). Our work provides an initial glimpse across an array of motor circuits including the upstream processing of the GF-mediated escape circuit, and pattern generators driving flight and seizure discharges.…”
Section: Discussionmentioning
confidence: 99%